CONTEMPORARY FATWA AGAINST ISTINBAT APPROACH ISSUES OF CURRENT JURISPRUDENCE-ORIENTED SCIENCE AND TECHNOLOGY - Dr Mohammad Azam Hussain; Prof. Madya Dr Alias Azhar (Journal of Islamic, Social, Economics and Development, 2016)
The science and technology dynamics (S & T) have affected the change of Islamiclaw and the legal authority that also opens the door for legal review. Fatwa istinbat in theframework of contemporary ijtihad is very important in order to provide clear and realisticlegal answers to current conditions. To form the foundation of the concept and the theory ofthis study, reference has been made to literary materials in library savings, important andofficial documents such as minutes of meetings, research reports, statistics, official documentsVolume: 1 Issue: 2 [December, 2016] pp.01-07]Journal of Islamic, Social, Economics and DevelopmenteISSN: 0128-1755Journal homepage: www.jised.com2of the Department of Islamic Development Malaysia and the Mufti departments. The conceptsand definitions of fatwa and the close relationship between ijtihad and fatwa serve as thebasis of the discussion theory of this article. Fatwa changes occur based on time changes,places, conditions and 'implications of scientific and technological developments. The basicneeds that need to be done to implement the Islamic law as a whole is the need to conduct theistiwabat fatwa in the framework of contemporary ijtihad. This requirement is aimed atbecoming a progressive Islamic law and able to deal with new legal issues, thereby beingpracticed at all times and places.